Po uptake in microalgae at different seawater pH: An experimental study simulating ocean acidification. (February 2020) - Uddin, S.; Bebhehani, M.; Al-Musallam, L.; Kumar, V.V.; Sajid, S.
Abstract: Climate change effects such as ocean acidification (OA) are known to affect the trace metal distribution. This experimental study provides the first data on 209 Po uptake rates and 210 Po concentration in five microalgae species under different pH scenarios. The experiment was conducted in replicates at three pH conditions 8.2, 8.0, and 7.5, representing the current and future climate change scenario as per IPCC RCP8.5. The 209 Po uptake in the phytoplankton was highest in Thalassiosira weissflogi, i.e. 83% of the 209 Po tracer was taken up at 8.2 pH whereas the lowest uptake was observed in Dunaliella salina equivalent to 20% at 7.5 pH. Similar behavior was observed in 210 Po concentrations in these microalgae, where 210 Po ranged between 3.16 ± 0.03 and 11.6 ± 0.04 Bq kg − 1 wet weight (ww), with the highest in the Thalassioria weissflogi at 8.2 pH, and the lowest in Dunaliella salina at 7.5 pH. The difference in 209 Po uptake and 210 Po concentration was statistically significant (p < 0.001) both among species and the pH treatments in the order: Thalassiosira weissflogi  >  Tetraselmis suecica  >  Chaetoceros muelleri  >  Isochrysis galbana  >  Dunaliella salina and 8.2 > 8.0 > 7.5. A higher concentration of 209 Po in seawater was measured at low pH condition in all the experimental tanks. Though the data clearly show the difference in concentration and uptake of polonium at different pH conditions, it is not known if lower pH is affecting the adsorbed or absorbed fraction. A detailed investigation will be required to understand the process as it can have a significant effect on biomagnification and marine food chain transfer under changing climatic scenarios. Highlights: Study provides insight on 210 Po concentration and likely uptake by phytoplankton under OA scenarios Lower 210 Po and 209 Po levels in microalgae were observed at low pH conditions Differences in 210 Po concentrations in microalgae species at different pH were statistically significant after 96-h exposure Final seawater 210 Po concentration was low at 8.2 compared to 7.5 in all experimental tanks